30 Cold-Water Corals as Shelter, Feeding and Life-History Critical Habitats for Fish Species: Ecological Interactions and Fishing Impact - D’Onghia, Gianfranco (Springer, 2019)
This chapter is a review of studies that present the role of cold-water corals as shelter, feeding and life-history critical habitats for fish species in the Mediterranean Sea and world oceans. Studies in the Mediterranean have been carried out both in Madrepora-Lophelia dominated communities and in coral areas characterised by octocorals and black corals. Most studies in the northeast Atlantic regard Lophelia pertusa reefs, while those in the northwest Atlantic refer to Oculina varicosa, L. pertusa and octocoral species. Octocorals and black corals dominated in the studies from the northeast Pacific. Most studies show that the cold-water coral habitats are important for fish species. In fact, a variety of fish species have been observed and suggested to benefit from shelter and productive feeding in the complex heterogeneous habitats built by corals. This is due to the enhanced density of zooplankton as potential prey for planktivorous fish and high density of invertebrates between and around corals as food for benthos feeders and scavengers. Moreover, several fish species use cold-water coral habitats as a spawning area and nursery. The occurrence of gravid individuals frequently observed in the coral habitats, as well as the presence of egg masses found deposited on coral stalks and egg cases attached to corals or found nested in coral colonies are clear evidence that several fish species rely on coral habitats as a place to spawn and protect offspring. The fish species of families Scyliorhinidae, Sebastidae, Serranidae, Berycidae, Zoarcidae, Lotidae, Moridae, Congridae, Liparidae seem to be more tightly associated to cold-water coral habitats. Some fish species of these families obtain multiple benefits from their association with cold-water coral habitats, despite being facultative inhabitants. Regarding the occurrence of many commercial fish species in cold-water coral habitats, it should be take into consideration that these habitats are highly impacted in the Mediterranean and throughout the oceans in ...